2021
DOI: 10.1111/1348-0421.12887
|View full text |Cite
|
Sign up to set email alerts
|

Current situation of carbapenem‐resistant Enterobacteriaceae and Acinetobacter in Japan and Southeast Asia

Abstract: In the recent years, issues related to drug-resistant bacteria have evolved worldwide, and various countermeasures have been taken to control their spread. Among a wide variety of drug-resistant bacterial species, carbapenem-resistant Gram-negative bacteria, including carbapenem-resistant Enterobacteriaceae (CRE) and carbapenemresistant Acinetobacter baumannii (CRAb), are those for which countermeasures are particularly important. Carbapenems are the last resort antibiotics for any bacterial infection; therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 65 publications
(160 reference statements)
1
8
0
1
Order By: Relevance
“…Data from National Antimicrobial Resistance Surveillance center, Thailand (NARST) show an exponential rise in the percentage of carbapenem-resistant Enterobacterales from 2015 to 2020 [ 14 ]. Similar findings have been reported in Japan and other parts of Southeast Asia, reflecting the ICU crisis in the region [ 15 ].…”
Section: Discussionsupporting
confidence: 88%
“…Data from National Antimicrobial Resistance Surveillance center, Thailand (NARST) show an exponential rise in the percentage of carbapenem-resistant Enterobacterales from 2015 to 2020 [ 14 ]. Similar findings have been reported in Japan and other parts of Southeast Asia, reflecting the ICU crisis in the region [ 15 ].…”
Section: Discussionsupporting
confidence: 88%
“…In previous studies, considerable differences in AMR rates have been reported for different countries [ 37 , 38 , 39 , 40 ]. To provide an unbiased evaluation for our study, the AMR rates of P .…”
Section: Discussionmentioning
confidence: 99%
“…Carbapenems, glycopeptides and linezolid are mostly used only for the treatment of severe antibiotic-resistant infections and relatively infrequently for these drugs. Countries also have corresponding guidelines to guide the rational use of these antibiotics, such as the guidelines for vancomycin in the United States 30 , use and management of carbapenem antibiotics in Japan and Southeast Asian countries 31 .…”
Section: Discussionmentioning
confidence: 99%